Video-assisted thoracic surgery versus stereotactic radiotherapy - Canova, Stefania; Pirondini, Emanuele; Bidoli, Paolo; Colonese, Francesca; Cortinovis, Diego Luigi (Video-Assisted Thoracic Surgery, 2017)
Lung cancer is the major cause of cancer death worldwide. The improvements of radiological techniques and the employment of screening programs often allow an early diagnosis of this disease. Surgical resection is considered the gold standard in early stages. However, the employment of less invasive techniques, both surgical and non-surgical, increased in the last decades. Video-assisted thoracoscopic surgery (VATS) demonstrated to obtain similar survival outcomes with less post-operative complications compared to open thoracotomy. Stereotactic body radiotherapy (SBRT) improves overall survival over conventional radiotherapy and offers a better safety profile compared to surgery.